Application Counseling Cognitive Behavioral With Modeling Techniques In Setting Lesson Study To Invervene Self Aggresion In Class X MIA 1 Students Of SMA N 1 Sukasada - Safitri, Indah (Bisma The Journal of Counseling, 2018)
This study aims to determine the effectiveness of cognitive behavioral counseling with Modeling techniques in lesson study settings to intervene in student self-aggresion. The experimental design used was Pretest Postest Control Group Design. The sample of this study was class X MIA 1 SMA Negeri 1 Sukasada which was taken randomly from 6 class members of the population. The self aggresion data collection in this study used the Self Aggresion questionnaire. Hypothesis testing is carried out using the t-test. The results of the t-test obtained by thit amounted to 15.20 with a significance of <0.001. It identified that cognitive behavioral counseling with Modeling techniques in effective lesson study settings to intervene in self aggresion of students X MIA 1 Sukasada 1 Public High School.